Immigration from the Global South: Silenced Stories of Migrant Women in Spain - El Mouali Samadi, Fatiha (Geopolítica(s). Revista de estudios sobre espacio y poder, 2021)
The dominant political and media discourses – and even some academic publications – in Spain continue to deal with and speak of immigration from the South from a very biased perspective. This perspective is limited to mentioning the poor living conditions and the lack of human rights in the countries of origin as the main reasons for leaving, while avoiding talking about the involvement of the West in the creation of these factors and the expulsion of this population from their territories. The narratives used rarely mention the problems and structural obstacles encountered in destiny, presenting this just as an opportunity to embrace freedom and equality vetoed in the native countries. This article seeks to show from a critical perspective how often the migratory experience turns into experiences of maximum vulnerability, due to the legal structure that the foreigners law establishes and the social outlook towards immigrants, in general, and particularly female immigration.
Keywords: North-South relations; geopolitics; immigration; gender; speeches